Dual use of electronic nicotine delivery systems (ENDS) and smoked tobacco: a qualitative analysis. Issue 1 (1st February 2018) - Robertson, Lindsay; Hoek, Janet; Blank, Mei-Ling; Richards, Rosalina; Ling, Pamela; Popova, Lucy
Abstract : Introduction: Electronic nicotine delivery systems (ENDS) arguably pose fewer health risks than smoking, yet many smokers adopt ENDS without fully relinquishing smoking. Known as 'dual use', this practice is widespread and compromises the health benefits that ENDS may offer. To date, few studies have explored how dual use practices arise and manifest. Methods: We conducted in-depth, semi-structured interviews with 20 current ENDS users from New Zealand who reported smoking tobacco at least once a month. We explored participants' smoking history, their recent and current smoking, trial, uptake and patterns of ENDS use, and future smoking and vaping intentions. We managed the data using NVivo V.11 and used a thematic analysis approach to interpret the transcripts. Results: Dual use practices among participants evolved in four ways. First, as an attempt to manage the 'inauthenticity' of vaping relative to smoking and to retain meaningful rituals. Second, as complex rationalisations that framed decreased tobacco use, rather than smoking cessation, as 'success'. Third, as a means of alleviating the financial burden smoking imposed and to circumvent smoke-free policies. Lastly, dual use reflected attempts to comply with social group norms and manage stigma. Conclusions: Dual use reflects both social and physical cues. It assisted participants to navigate smoking restrictions and allowed them to manage divergent norms. Policies that discourage smoking, particularly excise tax increases on smoked tobacco and smoke-free space restrictions, appear important in prompting ENDS use. Future research could explore whether these policies also help foster complete transition from smoking to exclusive ENDS use.